The effect of scrubber water from cruise ships in the ports of Stockholm - Bolin, Anton; Ekström, Oscar (My University, 2022)
Scrubbers are used onboard ships to clean the exhaust gases from sulphuric compounds, since this allows ships to use cheaper fuels that do not meet the regulations regarding the sulphur content in the fuel. The problem with scrubbers is that they move the emissions from the air to the sea instead. In this report, models of two ports in Stockholm were defined in the software Marine Antifoulant Model for Predicted Environmental Concentration (MAMPEC). Then, the concentrations of a selected number of metals and Polycyclic Aromatic Hydrocarbons (PAHs) in the discharge water were applied in the model to calculate the predicted environmental concentrations within the specific ports. The result shows higher concentrations in the Stockholm ports compared to the OECD-EU model port, with the highest concentrations in Värtahamnen. The result also shows that the OECD-EU port is not suited as a representative for the ports of Stockholm or any other small, confined ports in the Baltic Sea area due to the small water volumes and low water exchange. In some cases, the predicted concentrations reached levels high enough so that they may impact the marine ecosystem and even exceed the limits defined in the Water Framework Directive, yielding an unacceptable risk to the environment. The importance of this is that when legislation regarding scrubber water discharge is made it is crucial to consider different ports and not only the OECD-EU port. This report focus on the ports of Stockholm and cruise ships since there are several hundred arrivals per year and several of the cruise ships are equipped with scrubbers.
Keywords: Scrubber; Environmental impact; Ship pollution; Risk assessment